Comparison of Different Drying Methods for Asparagus [Asparagus cochinchinensis (Lour.) Merr.] Root Volatile Compounds as Revealed Using Gas Chromatography Ion Mobility Spectrometry - Chen, Gan-Lin; Lin, Bo; Zheng, Feng-Jin; Yu, Wei-Hua; Fang, Xiao-Chun; Shi, Qian; Hu, Yi-Feng; Verma, Krishan K. (Frontiers in Nutrition, 2022)
Asparagus (Asparagus cochinchinensis (Lour.) Merr.) is a traditional herbal medicine plant commonly used to nourish yin, moisten dryness, and clear fire cough symptoms. Drying is an excellent option to conserve food materials, i.e., grains, fruits, vegetables, and herbs, reducing the raw materials volume and weight. This study aims to evaluate different drying approaches that could increase the value of asparagus, particularly as an ingredient in fast foods or as nutraceutical byproducts. The volatile components of asparagus roots were analyzed by using headspace-gas chromatography-ion mobility spectroscopy (HS-GC-IMS) under different drying conditions, i.e., natural drying (ND) at ambient air temperature in the dark, well-ventilated room, temperature range 28-32 °C, blast or oven drying at 50 °C (BD), heat pump or hot-air drying (HPD) at temperature 50 °C and air velocity at 1.5 ms-1 and vacuum freeze-drying (VFD) at the temperature of -45 °C and vacuum pressure of 10-30 Pa for 24 h. The findings revealed that the various drying processes had multiple effects on the color, odor index, and volatile compounds of the asparagus roots. As a result of the investigations, multiple characteristics of components, therefore, exploitation and comparison of various flavors; a total of twenty-two compounds were identified, such as alcohols, ketones, aldehydes, acids, esters, heterocyclic, and terpene. The present findings may help understand the flavor of the processed asparagus roots and find a better option for drying and processing.